Overload Monitoring and Warning System for 3-Phase Electric Motorcycle based on IoT - Adhimanata, Yogi; Sulistiyowati, Indah; Wisaksono, Arief; Ayuni, Shazana Dhiya; Nasar, Muhammad (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
This research aims to develop and test a Telegram-based monitoring and overload warning system for three-phase motors, utilizing the PZEM-004T sensor and ESP8266 WiFi microcontroller, which is able to measure electrical parameters such as current, voltage, and power in real-time. The method used is a quantitative approach with an experimental method, where this system provides automatic notifications via the Telegram application in the event of an overload with a current limit of 20A, and is able to automatically cut off electricity to prevent more serious damage. Given the risk of overload that can cause production damage and costly downtime to the industry, the results show the effectiveness of the system in recording data and detecting overload conditions, although there are power measurement discrepancies that indicate the need for further calibration. Recommendations from this research include developments to improve measurement accuracy, standardization of procedures, and integration with relevant industry standards, as well as additional trials with different load variations to validate the system's performance in various scenarios.